PENGABDIAN KEPADA MASYARAKAT : DIVERSIFIKASI PENGOLAHAN RUMPUT LAUT EUCHEUMA COTTONII SEBAGAI TEH KOMBUCHA BERBASIS HEALTHY DRINK PADA MASYARAKAT PANTAI CEMARA PAKIS BANYUWANGI - Rachmawati, Nandya Fitri; Adharani, Nadya; Sakti, Widhi Winata; Chrissheila, Dea Eka; Febriyanto, Mohammad (Jurnal Abdi Insani, 2024)
Cemara Beach is a beach located in Pakis Village of Banyuwangi Regency, East Java. The catches of Cemara Beach fishermen are mostly fish and seaweed. The seaweed obtained by Cemara Beach fishermen is usually quite a lot when it has reached the seaweed catch season. The purpose of this service is to provide training and counseling on the processing of diversified seaweed products. Through the community of Cemara Beach can apply the results of this service for the welfare of the Cemara Beach community itself. The method of this service is a combination of anger, demonstration and direct practice. This is done by training and counseling using several stages, namely opening, core and closing regarding the processing of diversified Eucheuma cottonii seaweed products in the form of healthy drink Eucheuma cottonii seaweed kombucha tea . The results of this activity are 2 things. First: the community of Cemara Beach received training on the processing of diversified Eucheuma cottonii seaweed products in the form of healthy drink Eucheuma cottonii seaweed kombucha tea. Second: the people of Cemara Beach received counseling on appropriate technology in processing Eucheuma cottonii seaweed kombucha tea using a cabinet dryer. This cabinet dryer makes it easier for the people of Cemara Beach to dry seaweed which can beadjusted in time and temperature. Therefore, through this activity at Cemara Beach, the Cemara Beach community can obtain training and counseling on the processing of diversified Eucheuma cottonii seaweed products in the form of healthy drink Eucheuma cottonii seaweed kombucha tea and on appropriate technology in processing Eucheuma cottonii seaweed kombucha tea using a cabinet dryer.